2021
DOI: 10.1371/journal.pone.0246213
|View full text |Cite
|
Sign up to set email alerts
|

Sustained release buprenorphine effectively attenuates postoperative hypersensitivity in an incisional pain model in neonatal rats (Rattus norvegicus)

Abstract: Despite the need for safe and effective postoperative analgesia in neonates, research regarding pain management in neonatal rodents is relatively limited. Here, we investigate whether sustained release buprenorphine (Bup SR) effectively attenuates thermal hypersensitivity in a neonatal rat model of incisional pain. Male and female postnatal day 3 Sprague Dawley rat pups (n = 34) were randomly assigned to one of four treatment groups: 1) saline (control), 0.1 mL, once subcutaneously (SC); 2) buprenorphine HCl (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…However, due to the small hind paw size of neonatal rats, we modified the incisional pain model and performed a skin incision with dissection of the underlying muscle on the left thigh to increase the area for post-operative hypersensitivity testing. Previous studies by our lab have indicated that the thigh incisional pain model induces a post-operative thermal hypersensitivity response for 4 to 8 h in neonatal rats [ 19 , 20 ]. Previous work indicated that a diode laser provides sufficient stimuli to cause a withdrawal reflex to evaluate thermal hypersensitivity in adult rats [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, due to the small hind paw size of neonatal rats, we modified the incisional pain model and performed a skin incision with dissection of the underlying muscle on the left thigh to increase the area for post-operative hypersensitivity testing. Previous studies by our lab have indicated that the thigh incisional pain model induces a post-operative thermal hypersensitivity response for 4 to 8 h in neonatal rats [ 19 , 20 ]. Previous work indicated that a diode laser provides sufficient stimuli to cause a withdrawal reflex to evaluate thermal hypersensitivity in adult rats [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment groups consisted of: 1) Saline (Saline; 0.9% NaCl, Hospira, Lake Forest, IL) – 0.1 ml subcutaneous (SC) once ( n = 8), 2) Bup-SR (1 mg/mL)– 1mg/kg SC once ( n = 10), 3) XR-Lo (1.3 mg/mL) – 0.65 mg/kg SC once ( n = 10), 4) XR-Hi 1.3 mg/kg SC once ( n = 10). Doses of buprenorphine chosen were based on previous studies: 1) Bup-SR at 1 mg/kg was based on Blaney et al [ 20 ]; 2) XR-Hi at 0.65 and 1.3 mg/kg was based on doses in adult Sprague Dawley rats by Levinson et al [ 27 ] and Alamaw et al [ 28 ] (note that doses of XR-Hi in rat pups are not known).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations